1983
DOI: 10.1007/bf01413839
|View full text |Cite
|
Sign up to set email alerts
|

On vibrational states in deformed odd-A nuclei

Abstract: The equations for the description of vibrational states in deformed odd-A nuclei are obtained within the quasiparticle-phonon nuclear model. In these equations the Pauli principle is taken into account in the quasiparticle plus phonon components of the wave functions. It is shown that if in these components the Pauli principle is not violated or is slightly violated, the corresponding vibrational states may exist in deformed odd-A nuclei. If the Pauli principle is strongly violated in the quasiparticle plus ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This in turn may be very important, especially for the description of/?-and 7-vibrational transition probabilities. A similar effect has been well demonstrated in numerous calculations of these probabilities within the quasiparticle plus phonon model (QPM) for odd-A deformed nuclei [24][25][26][27]. The importance of vibrational admixtures in low-lying states of odd-odd nuclei has also been predicted in some phenomenological models [15,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…This in turn may be very important, especially for the description of/?-and 7-vibrational transition probabilities. A similar effect has been well demonstrated in numerous calculations of these probabilities within the quasiparticle plus phonon model (QPM) for odd-A deformed nuclei [24][25][26][27]. The importance of vibrational admixtures in low-lying states of odd-odd nuclei has also been predicted in some phenomenological models [15,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 77%
“…After the Valatin-Bogoliubov transformation from single-particle operators, a0 + , to the quasiparticle operators, c~, and using the RPA equations for one-phonon excitation of the even-even core, the intrinsic hamiltonian of (6) can be written in the form [26,33] …”
Section: Intrinsic Hamiltonian and Neutron-proton Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model takes account of the quasiparticle-phonon interaction, and the wave functions of excited states contain the sums of one-and two-phonon components [8,9]. it is shown that the inclusion of the Pauli principle in the two-phonon components of the wave functions [10] influences essentially the two-phonon collective states in doubly even nuclei [11] and some vibrational states in odd-A nuclei [12]. In Ref.…”
Section: Introductionmentioning
confidence: 99%